The anisotropic mechanical behaviour of passive skeletal muscle tissue subjected to large tensile strain - SIMMS, CIARAN; TAKAZA, MICHAEL (My University, 2013)
The passive mechanical properties of muscle tissue are important for many biomechanics applications. However, significant gaps remain in our understanding of the three-dimensional tensile response of passive skeletal muscle tissue to applied loading. In particular, the nature of the anisotropy remains unclear and the response to loading at intermediate fibre directions and the Poisson?s ratios in tension have not been reported. Accordingly, tensile tests were performed along and perpendicular to the muscle fibre direction as well as at 30, 45 and 60 degrees to the muscle fibre direction in samples of Longissimus dorsi muscle taken from freshly slaughtered pigs. Strain was measured using an optical non-contact method. The results show the transverse or cross fibre (TT?) direction is broadly linear and is the stiffest (77kPa stress at a stretch of 1.1), but that failure occurs at low stretches (approximately ? = 1.15). In contrast the longitudinal or fibre direction (L) is nonlinear and much less stiff (10kPa stress at a stretch of 1.1) but failure occurs at higher stretches (approximately? = 1.65). An almost sinusoidal variation in stress response was observed at intermediate angles. The following Poisson?s ratios were measured: ?LT = ?LT?= 0.47, ?TT?= 0.28 and ?TL= 0.74. These observations have not been previously reported and they contribute significantly to our understanding of the three dimensional deformation response of skeletal muscle tissue.
PUBLISHED
PMID: 23127635
Keywords: skeletal muscle tissue; Next Generation Medical Devices